Evolution der Gewalt - Ofner, Fritz (Austria, 2011)
Guatemala is considered one of the most dangerous countries in the world. Almost nowhere is the likelihood of falling victim to a violent crime. The Austrian ethnologist and documentary filmmaker places violence in the Central American country in the context of history as a "banana republic" in which the interests of foreign corporations determine politics. The film "Evolution of Violence" illustrates the culture of violence through four victims and actors.
Verzio Film Festival Submission
Keywords: Documentary films